Pseudohypoparathyroidism Type Ia and Pseudo‐Pseudohypoparathyroidism: The Growing Spectrum of GNAS Inactivating Mutations. Issue 3 (18th January 2013) - Elli, Francesca Marta; deSanctis, Luisa; Ceoloni, Barbara; Barbieri, Anna Maria; Bordogna, Paolo; Beck‐Peccoz, Paolo; Spada, Anna; Mantovani, Giovanna
<x xml:space="preserve">Abstract</x> Pseudohypoprathyroidism (PHP) is a rare heterogeneous genetic disorder characterized by end‐organ resistance to parathyroid hormone. Heterozygous inactivating GNAS mutations lead to either PHP type Ia or PPHP. The present work provides an updated collection of mutational and phenotypic data for both diagnostic and research purposes, as a step forward to a better understanding of PHP. The absence of genotype‐phenotype correlation supports the hypothesis of Gsα haploinsufficiency as the molecular mechanism underlying PHP, independently of the mutation type/localization. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>